2019
DOI: 10.1139/cjfas-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

A dam passage performance standard model for American shad

Abstract: Objectives for recovery of alosines commonly involve improving fish passage at dams during migration. However, a quantitative basis for dam passage performance standards is largely absent. We describe development of a stochastic life-history-based simulation model for American shad, Alosa sapidissima, to estimate effects of dam passage and migratory delay on abundance, spatial distribution of spawning adults, and demographic structuring in space and time. We used the Penobscot River, Maine, USA, as a case stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Simulation modeling suggested that migratory delays (especially downstream) are more detrimental than reduced passage for American Shad populations along the northeast Atlantic coast, as mortality reduces repeat spawners in iteroparous populations (Castro‐Santos and Letcher ; Stich et al. ). Nature‐like fishways may be an improvement for downstream passage over other fishway designs, as delays were minimal and passage efficiency was high for American Shad and Striped Bass at LD‐1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulation modeling suggested that migratory delays (especially downstream) are more detrimental than reduced passage for American Shad populations along the northeast Atlantic coast, as mortality reduces repeat spawners in iteroparous populations (Castro‐Santos and Letcher ; Stich et al. ). Nature‐like fishways may be an improvement for downstream passage over other fishway designs, as delays were minimal and passage efficiency was high for American Shad and Striped Bass at LD‐1.…”
Section: Discussionmentioning
confidence: 99%
“…Flathead Catfish predation on American Shad has also been observed by Ashley and Buff (1987) in the Cape Fear River and by Raabe and Hightower (2014a) in the Little River. Delays for American Shad can be especially detrimental in terms of energy loss, as they consume minimal food in rivers and are more likely to succumb to predation or harvest (Castro-Santos and Letcher 2010; Raabe and Hightower 2014a;Stich et al 2018). Detection records showed tagged American Shad (including ones at LD-1) being suddenly undetected in the array, indicating that they potentially succumbed to starvation, predation, or harvest.…”
Section: Passage Durationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In late summer and fall, the recently hatched juveniles migrate downstream to the ocean, at which point they typically range in size from 7 to 15 cm [6]. Most of these fish are iteroparous, so healthy population dynamics rely heavily on the successful downstream migration of both juveniles and adults [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Riverine spawning migrations of American Shad are relatively well characterized; fish passage preferences and information from directed fisheries and historical landings have also been examined (Moser et al 2000;Limburg et al 2003;Bailey et al 2004;Haro and Castro-Santos 2012;Grote et al 2014;Raabe and Hightower 2014;Waldman et al 2014). However, less is known about the interannual survival, movements, and behavior of postspawn American Shad outside of rivers (Leggett 1977;Melvin et al 1986;Dadswell et al 1987) despite a need for such information (ASMFC 2010; Hightower and Harris 2017; Stich et al 2019). Efforts to improve fish passage (where possible), closures of directed fisheries, and management of bycatch in nondirected fisheries have had limited success, with most individual river stocks still being at or near historic lows (ASMFC 2007).…”
mentioning
confidence: 99%